2012
DOI: 10.1111/j.1464-410x.2012.11561.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and satisfaction profile, between penile prosthesis implantation and oral PDE5 inhibitor Tadalafil therapy, in men with nerve‐sparing radical prostatectomy erectile dysfunction

Abstract: What's known on the subject? and What does the study add?• Erectile dysfunction after nerve-sparing radical retropubic prostatectomy constitutes a challenge to the urologist.The mainstay of medical treatment after radical prostatectomy to restore spontaneous erectile function remains phosphodiesterase (PDE5) inhibitors, despite the fact that data from animal studies suggesting that PDE5 inhibitors can prevent smooth muscle apoptosis and fibrosis have not yet been extrapolated to humans because of a lack of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Conversely, other authors adopted validated questionnaires developed to assess the outcome of treatments other than PPI [8,12,13]; in a recently published series, for instance, 94% of 98 men who underwent PPI after radical prostatectomy reported being satisfied after treatment according to the validated EDITS score [8]. Similar results were also reported in previous series using the IIEF [13,23]. The use of either a non-validated questionnaire or a tool developed in a non-PPI population could lead to an improper estimation of patient satisfaction.…”
Section: Discussionsupporting
confidence: 60%
“…Conversely, other authors adopted validated questionnaires developed to assess the outcome of treatments other than PPI [8,12,13]; in a recently published series, for instance, 94% of 98 men who underwent PPI after radical prostatectomy reported being satisfied after treatment according to the validated EDITS score [8]. Similar results were also reported in previous series using the IIEF [13,23]. The use of either a non-validated questionnaire or a tool developed in a non-PPI population could lead to an improper estimation of patient satisfaction.…”
Section: Discussionsupporting
confidence: 60%
“…Recent literature shows that PDE5-Is are safe and effective in treating ED patients after RP. Once daily administration of PDE5-Is has been experimentally proven to have a protective role in ED, and early administration of PDE5-Is helps to prevent cavernosal hypoxia, which leads to smooth muscle apoptosis and penile fibrosis [8-11]. Although PDE5-Is are one of the standard treatments for ED after RP, consensus has not been reached on their use, such as when to start, which drug is best, which dosage to use, how long to use, and when to stop [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…They reported good sexual function (EPID score > 60) in 77% of men and treatment satisfaction in 94% (EDITS score > 50). Other studies have actually reported improved satisfaction for men undergoing early penile prosthesis insertion compared to those receiving sildenafil or intracavernosal injection therapy 6 months after radical prostatectomy [169,170].…”
Section: Penile Prosthesis Implantationmentioning
confidence: 97%